Metabolismo do Setor de Serviços no Amazonas - interdependência do comércio e indústria - Laís Cosmo Lopes (Universidade Federal do Amazonas, 2016)
The objective of this research is to analyze the implications of Amazonas processing industry for the main activities of the service sector. Specifically, will be identified the composition of the macroeconomic aggregates of the main activities of the manufacturing industry and of the service sector. With regard to methodology, will be used data from Tables of Amazon Features and Uses at basic prices for the year of 2006, which will be used intermediate consumption and value of industry production services and of the main activities of the manufacturing industry. In terms of results, it was realized that the manufacturing industry has significant implications for the performance of the service sector in the Amazonian economy, whose evidence is in how they make up the macroeconomic aggregates selected in this research. In terms of gross value of production, it was realized that the manufacturing industry has the highest percentage in the composition of the secondary sector, whose value was 99.93%. Similarly, gross production of services does not have significant dependence of the industry, since its availability is made, for the most part, by public administration services, trade and transport. In turn, it was realized that the inputs coming from the manufacturing sector has a significant importance in the composition of intermediate consumption both in services as in manufacturing, with values of 71.03% and 79.62%, respectively.